Experience of some countries in the evaluation of research in universities and suggestions for Vietnam - Ngoc, Tran Hau; Thao, Pham Xuan; Ngoc, Nguyen Bao (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
By means of document analysis, the authors of this article presented an extensive experience of the Netherlands, the United Kingdom, Denmark and Australia - four of the countries which had established the evaluation system of research activities in universities in a comprehensive way, at national level - with the content including starting time and purpose of evaluation; main evaluation methods; and basic criteria of evaluation. From the analysis, the authors found advantages and challenges that the evaluation organizations was faced when performing evaluation of research, assessment of R&D organizations, in general and evaluation of research in universities, in particular. The study also reflected some remarks, made recommendations in connection to the preparation and implementation of the evaluation as mentioned above so as that it would be appropriate to practical conditions of present Vietnam for better management of science and technology (S&T). Code: 15052501